Omnivorous Behaviour of the Agouti (Dasyprocta leporina): A Neotropical Rodent with the Potential for Domestication. (2nd May 2019) - Jones, Kegan Romelle; Lall, Kavita Ranjeeta; Garcia, Gary Wayne
Abstract : The agouti is a Neotropical rodent which is mainly utilized for its meat in rural communities. Recently, captive rearing of these animals by wildlife farmers have increased in the Neotropics. This short communication consists of observation of feeding behaviour of captive reared agoutis at the University of the West Indies Field Station in Trinidad and Tobago. This is the first time in Trinidad and Tobago that meat consumption and the omnivorous behaviour of the agouti have been documented in the literature. The consumption of chicken ( Gallus domesticus ) eggs, dead chickens, and a brown dove ( Zenaida macroura ) by captive reared agoutis was noted. This document described the omnivorous behaviour of the agouti which is primarily considered a frugivorous animal. Similar studies in South America have shown that wild and captive reared agoutis consumed animal matter. Further work must be done on the dietary needs and nutrient requirements of the agouti at different physiological states.